2013
DOI: 10.1136/emermed-2013-202813
|View full text |Cite
|
Sign up to set email alerts
|

Predictive accuracy of triage nurses evaluation in risk stratification of syncope in the emergency department

Abstract: Nursing triage was characterised by a low predictive accuracy in identifying high-risk individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…A SAD was defined as: (f) haemorrhage causing haemodynamic instability or requiring emergency procedures (e.g. endoscopy); (g) acute neurological disorders; (h) sepsis or septic shock; or (i) urgent surgery in 48 h of the ED evaluation (Bonzi et al, 2014;Numeroso et al, 2017Numeroso et al, , 2019Numeroso et al, , 2021.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…A SAD was defined as: (f) haemorrhage causing haemodynamic instability or requiring emergency procedures (e.g. endoscopy); (g) acute neurological disorders; (h) sepsis or septic shock; or (i) urgent surgery in 48 h of the ED evaluation (Bonzi et al, 2014;Numeroso et al, 2017Numeroso et al, , 2019Numeroso et al, , 2021.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…First, the retrospective nature of the study exposes it to the possible bias associated with such a study design. Second, the choice of the acute diseases included in the composite outcome of the study was made a priori on the basis of the literature and similar existing studies (Bonzi et al, 2014;Numeroso et al, 2017Numeroso et al, , 2019Numeroso et al, , 2021. Third, the accuracy of nurse triage was not assessed through inter-rater reliability.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical bottom line-As it was demonstrated that nursing triage in ED can be inaccurate in identifying high-risk syncope patients [85], it is conceivable that the implementation of prognostic algorithms might lead to the future improvement of this ED operation, as already seen in other clinical conditions [86][87][88]. However, at the present state of the art, this application of ML has not yet been extensively studied and it is to be considered only experimental.…”
Section: Syncope Risk Stratification and Ed Dispositionmentioning
confidence: 99%
“…4 Specialist nurses have also been evaluated in triaging patients with syncope and have been found to have low predictive accuracy in identifying high-risk individuals. 5 There has also been a qualitative study of nurses' cardiac triage decisions and they found that the nurse's ultimate goal is to have the patient receive prompt electrocardiography and prompt medical evaluation and to advocate for the patient. 6 While nurses are aware of age and sex differences in myocardial infarction presentation, some nurses still hold cultural biases and stereotypes that may interfere with timely delivery of emergency cardiac healthcare.…”
mentioning
confidence: 99%